INTERNATIONALIZATION OF HOSPITALITY EDUCATION IN TAIWAN: THE CAST AT A PUBLIC UNIVERSITY - HSIAO-I HOU (Centre For Tourism Planning and Development, 2011)
The main purpose of this study is to explore the ways in which internationalization of hospitality education in Taiwan has grown and changed over time. Literature related to recent strategies and policies in internationalizing Taiwan's higher education and hospitality education are reviewed. A qualitative case study approach was adopted to learn what strategies a public vocational university has adopted to make it successful. The findings shows that some patterns of development are identified, and numerous strengths and challenges in institutional strategies are revealed. An in-depth critical analysis of the case leads to recommendations for institutional governance and operations in internationalization initiatives.